Anti-tumor effect of CT-322 as an adnectin inhibitor of vascular endothelial growth factor receptor-2 - Mamluk, Roni (Landes Bioscience, 2010)
CT-322 is a new anti-angiogenic therapeutic agent based on an engineered variant of the tenth type III domain of human fibronectin, i.e., an Adnectin™, designed to inhibit vascular endothelial growth factor receptor (VEGFR)-2. This PE Gylated Adnectin was developed using an mRNA display technology. CT-322 bound human VEGFR-2 with high affinity (K(D), 11 nM), but did not bind VEGFR-1 or VEGFR-3 at concentrations up to 100 nM, as determined by surface plasmon resonance studies. Western blot analysis showed that CT-322 blocked VEGF-induced phosphorylation of VEGFR-2 and mitogen-activated protein kinase in human umbilical vascular endothelial cells. CT-322 significantly inhibited the growth of human tumor xenograft models of colon carcinoma and glioblastoma at doses of 15–60 mg/kg administered 3 times/week. Anti-tumor effects of CT-322 were comparable to those of sorafenib or sunitinib, which inhibit multiple kinases, in a colon carcinoma xenograft model, although CT-322 caused less overt adverse effects than the kinase inhibitors. CT-322 also enhanced the anti-tumor activity of the chemotherapeutic agent temsirolimus in the colon carcinoma model. The high affinity and specificity of CT-322 binding to VEGFR-2 and its anti-tumor activities establish CT-322 as a promising anti-angiogenic therapeutic agent. Our results further suggest that Adnectins are an important new class of targeted biologics that can be developed as potential treatments for a wide variety of diseases.